From Awareness to Practice: Addressing Behavior, Accommodations, and Universal Design for Learning - Lily Eka Sari; Fiona Christie Antoro; Christy Imanuella Sampouw; Jeremy Chrystofer (Universitas Negeri Surabaya, 2026)
Inclusive education requires serious collaborative efforts. Teachers often find significant issues in terms of designing and carrying out learning process. This is a case study regarding major issues which occur in a private school in Surabaya, Indonesia. Based on the mapping of the themes, there were three issues which were considered urgent to address, namely: behavior, accommodation, and Universal Design for Learning. This study made attempts to bridge existing theories and their implications in the field.